Respiratory Support in Bronchiolitis: Trial Evidence - Cunningham, Steve (American Journal of Perinatology, 2018)
Acute viral lower respiratory tract infection is frequently associated with hypoxemia and respiratory distress, sometimes progressing to hypercarbia and respiratory failure. In recent years, trials have assessed the effects of oxygen supplementation and respiratory support with high-flow oxygen therapy. An oxygen saturation target of 90% is as safe and clinically effective as 94% in infants with bronchiolitis. Trials of high-flow humidified oxygen have demonstrated safety, but as yet poorly demarcated an appropriate place for use within the clinical course of the disease. Effective trials of continuous positive airway pressure are lacking and urgently required. The trials reported to date have highlighted the need for common outcomes in relation to treatment failure.
Keywords: bronchiolitis; oxygen; CPAP; high flow oxygen therapy